FOREIGN POLICY IN THE BOLSONARO GOVERNMENT FOR ISRAEL: THE TWO-LEVEL GAME AND PENTECOSTAL INFLUENCE - Nadir, Mohammed; Henrique Thuler de Oliveira, Pedro (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2025)
President Jair Bolsonaro's government saw several ruptures in relation to the political tradition of Brazilian diplomacy, and nowhere was this as clear as in the changes that occurred in the long relationship between Brazil and the State of Israel. Using Robert Putnam's Two-Level Game theory, this work aims to understand the influence that changes in the domestic context caused by Bolsonaro's election motivated this rapprochement with the State of Israel, especially taking into account the influence that Pentecostal and neo-Pentecostal groups exerted throughout this process.